2021
DOI: 10.1186/s41927-020-00172-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Behçet’s disease: clinical characteristics, diagnostic criteria, and differential diagnoses

Abstract: Background The diagnosis of Behçet disease (BD) is challenging in many cases. The purpose of this study was to describe the clinical characteristics of patients at a referral BD clinic. Methods In a retrospective study, we collected data from patients at a national referral Behçet clinic from November 2018–August 2019. A BD diagnosis was confirmed (BD group) or ruled out (Non-BD group), and the two groups were compared for differences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 16 publications
0
40
0
1
Order By: Relevance
“…Here, we report a case of intestinal BD that was successfully treated with IFX. This case was diagnosed as intestinal BD according to the international diagnostic criteria for BD (2). Our qPCR analyses of colonic biopsy samples revealed that the colonic mucosa of this patient was characterized by increased expression levels of IL-17, IL-23, TNF-α, IFN-β, CXCL9, and CXCL10 before treatment.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Here, we report a case of intestinal BD that was successfully treated with IFX. This case was diagnosed as intestinal BD according to the international diagnostic criteria for BD (2). Our qPCR analyses of colonic biopsy samples revealed that the colonic mucosa of this patient was characterized by increased expression levels of IL-17, IL-23, TNF-α, IFN-β, CXCL9, and CXCL10 before treatment.…”
Section: Discussionmentioning
confidence: 88%
“…These endoscopic and pathological findings were not consistent with Crohn's disease or ulcerative colitis. Based on the presence of uveitis, oral ulcers, and intestinal symptoms, the patient was diagnosed with intestinal BD according to the international diagnostic criteria for BD (2).…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous COPCORD studies performed in Iran have shown a 30–50% prevalence of musculoskeletal complaints, 15–25% for degenerative joint diseases, and approximately 1% for rheumatologic disorders [ 6 , 11 , 12 ]. Therefore, with a 5% type I error and an absolute error of 5%, this study would need > 138 individuals for a disease with 10% prevalence (e.g., musculoskeletal complaints), and > 1382 individuals for 1% prevalence (e.g., rheumatologic diagnoses).…”
Section: Methodsmentioning
confidence: 99%
“…BD begins between the ages of 20 and 40, but early and late onsets have been reported in some studies. 1 Because of the lack of pathognomonic laboratory tests, the diagnosis is based on related clinical findings. The International Working Group (ISG) diagnostic criteria, which published in 1990, continue to be the most widely accepted criteria among experts in BD.…”
Section: Introductionmentioning
confidence: 99%